Soil organic matter on arid saline-alkali land drives greenhouse gas emissions from artificial and natural grasslands in different directions - Wei, Ziwen; Cheng, Yunxiang; Hou, Fujiang (Frontiers in Environmental Science, 2024)
Reducing greenhouse gas (GHG) emissions and mitigating the pace of global warming are crucial to achieving a balance between economic development and ecological protection. However, research on GHG emissions from different types of artificial grasslands is limited. This study aimed to elucidate the dynamics of GHG emission fluxes in three types of artificial grasslands and natural saline meadow grassland (NG). Meteorological and soil data were collected to determine the correlations between GHG fluxes and environmental variables. All grasslands were sources of CO2 and N2O. Artificial grasslands were sinks of CH4, whereas NG was a CH4 source. FCO2 was the main source of GHGs in grasslands. The average emissions of FCO2 and FN2O in artificial grasslands were higher than those in NG. Soil temperature had a positive effect on GHG emissions in all grasslands and soil organic matter content was the main factor affecting all grassland GHG fluxes.Soil Research and Rehabilitation 14(3), 281-292.